2008
DOI: 10.1111/j.1365-2869.2008.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Arousal and ventilatory responses to mild hypoxia in sleeping preterm infants

Abstract: SUMMARY A failure to adequately respond to hypoxia has been implicated in the Sudden Infant Death Syndrome (SIDS). Preterm infants are at increased risk for SIDS, thus we compared ventilatory and arousal responses to mild hypoxia [15% oxygen (O 2 )] in preterm and term infants. Eight preterm and 15 term infants were serially studied with daytime polysomnography during which nasal airflow was monitored by pneumotachograph at 2-5 weeks, 2-3 and 5-6 months. At each age, in both groups, hypoxia induced a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 38 publications
0
14
1
1
Order By: Relevance
“…Arousals and increased ventilatory response characterized by changes in respiratory rate and rhythm have been seen in hypoxia and hypercarbia in both animal and human adult and infant studies (8,30,31,36,37). In our study, separately as well as in parallel, upon spontaneous and induced esophageal stimulation, arousal responses have been noted in both quiet and active sleep states.…”
Section: Discussionmentioning
confidence: 51%
“…Arousals and increased ventilatory response characterized by changes in respiratory rate and rhythm have been seen in hypoxia and hypercarbia in both animal and human adult and infant studies (8,30,31,36,37). In our study, separately as well as in parallel, upon spontaneous and induced esophageal stimulation, arousal responses have been noted in both quiet and active sleep states.…”
Section: Discussionmentioning
confidence: 51%
“…Research in this area has focused on physiological responses to air challenges. In term infants, normal biphasic responses to hypoxia were present at 2–5 weeks, 2–3 months, and 5–6 months postnatal (Richardson et al, 2007; Verbeek et al, 2008). In preterm infants, the ventilatory response to hypoxia appears to transition from a monophasic depressive response at 31.5 weeks post-conception (Alvaro et al, 1992) to a biphasic response by 35.5 weeks post-conception (Martin et al, 1998) and is still present at 45 weeks post-conception (Verbeek et al, 2008).…”
Section: Prematurity and Sidsmentioning
confidence: 99%
“…In term infants, normal biphasic responses to hypoxia were present at 2–5 weeks, 2–3 months, and 5–6 months postnatal (Richardson et al, 2007; Verbeek et al, 2008). In preterm infants, the ventilatory response to hypoxia appears to transition from a monophasic depressive response at 31.5 weeks post-conception (Alvaro et al, 1992) to a biphasic response by 35.5 weeks post-conception (Martin et al, 1998) and is still present at 45 weeks post-conception (Verbeek et al, 2008). The early monophasic depressive response may reflect the transition from fetal-like to neonatal respiratory and autonomic function in preterm infants (Boddy et al, 1974; Alvarez et al, 1992) and is similar in some ways to the attenuated ventilatory augmentation seen in anesthetized infants and animal models after prenatal nicotine exposure (Ueda et al, 1999; Hafstrom et al, 2002; Sawnani et al, 2004; Eugenin et al, 2008).…”
Section: Prematurity and Sidsmentioning
confidence: 99%
“…Moreover, preterm infants (26-32 weeks of gestation) with a history of apnoea and bradycardia of prematurity showed decreased responses in both active sleep and quiet sleep at term, and in quiet sleep at 2-3 months post-term (Horne et al, 2001). After a mild hypoxia challenge (15% oxygen), preterm infants had a longer arousal latency in active sleep at 2-3 weeks of age and reached significantly lower SpO 2 levels at 2-5 weeks in both active sleep and quiet sleep and at 2-3 months in quiet sleep (Verbeek et al, 2008). The greater desaturation during the hypoxic challenge combined with the longer arousal latency suggested that in preterm infants there was an impairment or inadequate response to hypoxia during sleep, which may explain the enhanced risk for SIDS in this group.…”
Section: Sids Risk Factors and Preterm Birthmentioning
confidence: 94%